Effects of resisted sprint training on sprint, jump, and change-of-direction performance in athletes: a systematic review and meta-analysis - Li, Chengcheng; Chen, Lunxin; Zhang, Qin (Frontiers in Physiology, 2025)
ObjectiveTo systematically evaluate the effects of RST (resisted sprint training) on athletes’ sprint, jump, and COD (change-of-direction performance).MethodsFollowing PRISMA, we searched seven databases from inception to 12 July 2025—PubMed, Web of Science (all databases), MEDLINE, CENTRAL, SPORTDiscus, Scopus, and Embase. Study certainty was appraised with GRADE. All included data were analyzed in Stata/MP 18.0.ResultsSixteen studies (404 participants) were included. RST significantly improved linear sprint performance (SMD = 0.65, p < 0.001, I2 = 21.2%), vertical jump performance (SMD = −0.38, p = 0.013 I2 = 0.0%), and COD ability (SMD = 1.10, p < 0.001, I2 = 0.0%). UST (unresisted sprint training)also significantly improved linear sprint performance (SMD = 0.42, p < 0.001, I2 = 15.6%) and COD ability (SMD = 0.60, p < 0.001, I2 = 0.0%), but not vertical jump performance (SMD = −0.03, p = 0.872, I2 = 0.0%). Compared with UST, RST produced a greater improvement in COD ability (p = 0.043), with no significant differences for linear sprint (p = 0.057) or vertical jump (p = 0.102). Subgroup analyses indicated that, relative to UST, RST had larger benefits for 0–10 m linear sprint performance (p < 0.001) and among youth athletes (p = 0.000). Versus RT (regular training), RST yielded greater improvements in linear sprint performance (p < 0.001) and vertical jump performance (p < 0.001), but not in COD ability (p = 0.064).ConclusionBoth RST and UST improve linear sprint performance and COD ability. Only RST shows a significant within-group gain in vertical jump. Compared with UST, RST yields greater benefits for initial acceleration (0–10 m) and among youth athletes. Practically, when the primary goal is initial acceleration and COD, prioritize RST; for broader explosive-power development, pair RST with vertically oriented strength or plyometric training to develop both horizontal and vertical force qualities.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#guidancenotes, identifier PROSPERO (CRD420251103833).